A QoE-based approach for multiple description coding (MDC) streaming over video distribution network (VDN). (1st January 2011) - Ghareeb, Majd; Viho, Cesar
In the last decade, overlay multipath video streaming has appeared as a relevant solution to cope with network conditions' changing. However, the important challenge that still needs to be faced is how to split the video into alternative sub-streams and how to define the multiple paths. In this paper, we propose an approach that generates multiple complementary descriptions of the video based on the group of pictures (GOPs). Besides, we use the quality of experience (QoE) evaluations to adjust the streaming over multiple video distribution network (VDN) paths. For evaluating the QoE, different approaches have been tested before adopting the pseudo-subjective quality assessment (PSQA) tool as the best-suited tool for our approach. Results show the automatic adaptability of the proposed method to network bandwidth fluctuation. They also show the advantages of using multiple description coding (MDC), against the traditional multi-streams splitting strategies, especially in overloaded environments.